Nas fissuras do agrohidronegócio brotam territorialidades de esperança em Mucugê-Bahia - Oliveira, Débora Paula de Andrade (2022)
The objective of this thesis is to understand the territorialities of hope created by peasant family farmers in the context of the transformations resulting from the expansion of agrohydrobusiness in the municipality of Mucugê, Chapada Diamantina, Bahia, Brazil. It seeks to analyze, from the perspective of the social subjects of peasant family agriculture, these territorialities, understood as alternative strategies for the maintenance and social reproduction of life, which are based on the link with identity with the territory and the symbolic dimension of work on the land, elaborated in their daily social practices and with the know-how learned in the contexts of the community and the family group in the countryside. The thesis is anchored in a qualitative and critical analysis of reality. With regard to theoretical and methodological aspects, the territory was listed as a central category of analysis, linked to discussions on territoriality and territorial identity, read as essential links with the lived dimension of the territory. To reflect at the conceptual level on the territorialities of hope, it was based on the understanding of “esperançar” (build hope) as a movement of collective struggle and the organization of people for the common good. The theoretical discussion about the agrarian question and agrohydrobusiness was based on the reading of the contradictions intrinsic to the reproduction and expansion of the contradictions of capitalism in the countryside. At the same time, we sought to systematize secondary data related to the social conditions of life of the local population, in addition to mapping and field research in loco, which involves observations, dialogues and experiences, in addition to conducting semi-structured interviews. In reading the reality in question, it was found that the agrohydrobusiness transformed the rural territories of Mucugê, imposing capitalist logics of work on the land. In addition to the social repercussions related to the exploitation and precariousness of the workforce in the countryside, there was also the degradation of environments with the risk of contamination of natural resources with the application of pesticides used in the English potato monoculture crops. The implementation of the Apertado Dam, in 1998 accentuated the process of territorial domination and land concentration in the municipality, in order to reduce the territory destined for family agriculture, which, even in such unfavorable conditions, r-exists. In this r-existence, alternative forms of work and life persist based on peasant sociability, with agroecological and solidarity economy initiatives based on collective work in rural communities. Local socioeconomic indices reflect the social contradictions intrinsic to agrohydrobusiness, in which it was possible to prove that the stated wealth and development proclaimed by agrohydrobusiness advocates have rarely contributed to improving the living conditions of the local population. The creation of territorialities of hope by the subjects of peasant family farming constitutes a strategy of social reproduction and permanence in their territories of life and work in the countryside.